The Association of Therapist Empathy and Synchrony in Vocally Encoded Arousal - Imel, Zac E. (2013)
Empathy is a critical ingredient in motivational interviewing (MI) and in psychotherapy generally. It is typically defined as the ability to experience and understand the feelings of another. Basic science indicates that empathy is related to the development of synchrony in dyads. However, in clinical research, empathy has proved difficult to operationalize and measure, and has mostly relied on the felt sense of observers, clients, or therapists. We extracted estimates of therapist and standardized patient (SP) vocally encoded arousal (mean fundamental frequency; mean f(0)) in 89 MI sessions with high and low empathy ratings from independent observers. We hypothesized (a) therapist and SP mean f(0) would be correlated and (b) the correlation of therapist and SP mean f(0) would be greater in sessions with high empathy as compared with low. On the basis of a multivariate mixed model, the correlation between therapist and SP mean f(0) was large (r = .71) and close to 0 in randomly assigned therapist–SP dyads (r = −.08). The association was higher in sessions with high empathy ratings (r = .80) than in sessions with low ratings (r = .36). There was strong evidence for vocal synchrony in clinical dyads as well as for the association of synchrony with empathy ratings, illustrating the relevance of basic psychological processes to clinical interactions. These findings provide initial evidence for an objective and nonobtrusive method for assessing therapist performance. Novel indicators of therapist empathy may have implications for the study of MI process as well as the training of therapists generally.